Role of neutrophils in tuberculosis: A bird's eye view - J Nancy Hilda; Sulochana Das; Srikanth P Tripathy; Luke Elizabeth Hanna (Innate Immunity, 2020)
Neutrophils are innate immune cells implicated in the process of killing Mycobacterium tuberculosis early during infection. Once the mycobacteria enter the human system, neutrophils sense and engulf them. By secreting bactericidal enzymes and α-defensins like human neutrophil peptides loaded in their granule armory, neutrophils kill the pathogen. Peripheral blood neutrophils secrete a wide range of cytokines like IL-8, IL-1-β and IFN-γ in response to mycobacterial infection. Thus they signal and activate distant immune cells thereby informing them of prevailing infection. The activated monocytes, dendritic cells and T cells further continue the immune response. As a final call, neutrophils release neutrophil extracellular traps in circulation which can trap mycobacteria in patients with active pulmonary tuberculosis. Extensive neutrophilic response is associated with inflammation, pulmonary destruction, and pathology. For example, inappropriate phagocytosis of mycobacteria-infected neutrophils can damage host cells due to necrosis of neutrophils, leading to chronic inflammation and tissue damage. This dual nature of neutrophils makes them double-edged swords during tuberculosis, and hence data available on neutrophil functions against mycobacterium are controversial and non-uniform. This article reviews the role of neutrophils in tuberculosis infection and highlights research gaps that need to be addressed. We focus on our understanding of new research ideologies targeting neutrophils (a) in the early stages of infection for boosting specific immune functions or (b) in the later stages of infection to prevent inflammatory conditions mediated by activated neutrophils. This would plausibly lead to the development of better tuberculosis vaccines and therapeutics in the future.